A spliceosome intermediate with loosely associated tri-snRNP accumulates in the absence of Prp28 ATPase activity - Carsten Boesler (Nature Portfolio, 2016)
The assembly of the splicesome involves several distinct stages that require the sequential action of DExD/H-box RNA helicases. Here, the authors uncover a new intermediate, the pre-B complex, that accumulates in the presence of an inactive form of the DEAD-box protein Prp28.